2010
DOI: 10.1111/j.1540-6261.2010.01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Sellers and Financial Misconduct

Abstract: We examine whether short sellers detect firms that misrepresent their financial statements, and whether their trading conveys external costs or benefits to other investors. Abnormal short interest increases steadily in the 19 months before the misrepresentation is publicly revealed, particularly when the misconduct is severe. Short selling is associated with a faster time-to-discovery, and it dampens the share price inflation that occurs when firms misstate their earnings. These results indicate that short sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
259
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(274 citation statements)
references
References 53 publications
14
259
1
Order By: Relevance
“…8 Evidence of short arbitrage of accounting-related information includes Dechow et al (2001) for stocks with low fundamentalto-price ratios; Desai et al (2006) for restatement announcements; Karpoff and Lou (2010) for SEC enforcement actions; Hirshleifer et al (2011) for accruals;and Drake et al (2011) for analyst recommendations.…”
mentioning
confidence: 99%
“…8 Evidence of short arbitrage of accounting-related information includes Dechow et al (2001) for stocks with low fundamentalto-price ratios; Desai et al (2006) for restatement announcements; Karpoff and Lou (2010) for SEC enforcement actions; Hirshleifer et al (2011) for accruals;and Drake et al (2011) for analyst recommendations.…”
mentioning
confidence: 99%
“…The process of mining negative information by short sellers increases the risk that managers fail to disclose the positive information in time, so it will motivate managers to disclose information timely and accurately. Karpoff et al (2010) [4], Hirshleifer et al (2011) [5] found that short selling can restrain the financial fraud. Chen et al (2015) [12], Fang et al (2016) [13] found that short selling can restrain earnings management and improve the reliability of financial information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Karpoff, Lou (2010) [4], Hirshleifer et al (2011) [5], investigated the effect of short selling mechanism on the quality of financial information; Grullon et al (2015) [6] and Jin et al (2015) [7] examined the impact of short selling mechanism on corporate investment behavior. There is little literature on the impact of short-selling on executive pay contracts.…”
mentioning
confidence: 99%
“…6 Other market participants may also influence the shareholders of firms in this way; however, the short-selling channel is particularly powerful because short sellers are known to be good at processing negative information (e.g., Hirshleifer et al,, 2011;Karpoff & Lou, 2010). mechanism to monitor management via board representation.…”
Section: Iie3 Long-term Market-based Firm Performancementioning
confidence: 99%